Deciphering the divergent transcriptomic landscapes of cervical cancer cells grown in 3D and 2D cell culture systems - Roshan Kumar; Roshan Kumar; Roshan Kumar; Marissa Iden; Marissa Iden; Shirng-Wern Tsaih; Shirng-Wern Tsaih; Rachel Schmidt; Rachel Schmidt; Akinyemi I. Ojesina; Akinyemi I. Ojesina; Janet S. Rader; et al. (Frontiers in Cell and Developmental Biology, 2024)
Cervical cancer remains a significant health challenge for women worldwide, with a disproportionate impact on developing regions like sub-Saharan Africa. Taking advantage of recent advancements in developing suitable preclinical models to study cell proliferation, differentiation, and gene expression, we used RNA sequencing to compare the transcriptomic profiles of SiHa cervical cancer cells grown in 3D versus 2D culture systems. Pathway analysis of 3D cultures revealed upregulation of immune activation, angiogenesis, and tissue remodeling pathways. The high expression of cytokines, chemokines, matrix metalloproteinases, and immediate early genes, suggests that 3D cultures replicate the tumor microenvironment better than 2D monolayer cultures. HPV gene expression analysis further demonstrated higher expression levels of HPV16 E1, E2, E6, and E7 genes in 3D versus 2D cultures. Further, by using a set of linear models, we identified 79 significantly differentially expressed genes in 3D culture compared to 2D culture conditions, independent of HPV16 viral gene effects. We subsequently validated five of these genes at the protein level in both the SiHa cell line and a newly developed, patient-derived cervical cancer cell line. In addition, correlation analysis identified 26 human genes positively correlated with viral genes across 2D and 3D culture conditions. The top five 3D versus 2D differentially expressed and HPV-correlated genes were validated via qRT-PCR in our patient derived cell line. Altogether, these findings suggest that 3D cultures provide superior model systems to explore mechanisms of immune evasion, cancer progression and antiviral therapeutics.